1980
DOI: 10.4141/cjas80-048
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fiber Addition to Diets Formulated to Contain Different Levels of Energy and Protein on Growth and Carcass Quality of Swine

Abstract: KENNrlr-v, J. J. rNo AsrnNE, F. X. The effect of fiber addition to diets formulated to contain different levels of energy and protein on growth and carcass quality of swine. Can. J. Anim. .The influence of dietary crude fiber, and of the methods used in formulating high fiber diets, on the performance and carcass composition of swine was studied in an experiment in which 72 pigs were fed four diets. Diet l, the control, contained 14

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

1986
1986
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 23 publications
0
13
0
1
Order By: Relevance
“…The lower average daily weight gain recorded in this study might be due to the feeding of pigs with low energy and high fiber diet and the managemental practices adopted by the farmers. Reduction in growth rate and performance of pigs due to unconventional feeding has already been reported (Sharda et al, 1976;Kennedy and Sherne, 1980) and the reason attributed was the reduced energy level in the feed.…”
Section: Discussionmentioning
confidence: 88%
“…The lower average daily weight gain recorded in this study might be due to the feeding of pigs with low energy and high fiber diet and the managemental practices adopted by the farmers. Reduction in growth rate and performance of pigs due to unconventional feeding has already been reported (Sharda et al, 1976;Kennedy and Sherne, 1980) and the reason attributed was the reduced energy level in the feed.…”
Section: Discussionmentioning
confidence: 88%
“…The low average daily -fish integration 25 10 25 20 20 7000 30 Duck-fish integration 25 10 25 20 20 7000 300 Control 25 10 25 20 20 7000 -weight gain in the traditional feeding system might be due to the feeding of pigs with low energy and high fiber diet. Reduction in growth rate and performance of pigs due to traditional feeding has already been reported (Sharda et al 1976;Kennedy andSherne 1980, Kumaresan et al 2007) and the reason attributed was the reduced energy level in the feed.…”
Section: Discussionmentioning
confidence: 84%
“…However, the body weight of Hampshire and LWY pigs observed in the present study was lower than those reported earlier under standard management conditions, which might be due to difference in the feeding system. Reduction in growth rate of pigs due to unconventional feeding has already been reported (Kennedy and Sherne 1980) and the reason attributed was the reduced energy level in the feed.…”
Section: Discussionmentioning
confidence: 94%